Applications of Cucurbiturils in Medicinal Chemistry and Chemical Biology - Das, Debapratim; Assaf, Khaleel I.; Nau, Werner M. (Frontiers in Chemistry, 2019)
The supramolecular chemistry of cucurbit[n]urils (CBn) has been rapidly developing to encompass diverse medicinal applications, including drug formulation and delivery, controlled drug release, and sensing for bioanalytical purposes. This is made possible by their unique recognition properties and very low cytotoxicity. In this review, we summarize the host-guest complexation of biologically important molecules with CBn, and highlight their implementation in medicinal chemistry and chemical biology.